PEMBANGUNAN PERKERASAN JALAN BARU DI JALAN HARMONIKA BARU, PASAR II TANJUNG SARI, KECAMATAN MEDAN SELAYANG KOTA MEDAN - Haryanto, Zulfan; Daryanto, Eka; Mendoza, M Dominique (Jurnal Insinyur Profesional, 2025)
and activity of traffic flow every day along this road. Both traffic heading towards Tanjung Sari and traffic heading towards Jamin Ginting. The Medan City Government, North Sumatra through the Public Works Department took considerations, and policies and decided to open a new road and improve the pavement along the Harmonika Baru Pasar II Tanjung Sari-Setia Budi road as mentioned above. Therefore, this research is intended to assist the Medan City government in analyzing the detailed engineering design for widening the road. This research aims to carry out a detailed analysis of the engineering design of the new road pavement on Jalan Harmonika Baru, Pasar II Tanjung Sari, Medan Selayang District. Research analysis of the detailed engineering design of new road pavement was carried out on Jalan Harmonika Baru, Pasar II Tanjung Sari, Medan Selayang District with a length of 1,705 m. The results of calculations from field research show that the condition of the road meets the applicable provisions and requirements set by Bina Marga. In this design, a surface layer thickness of 5 cm is obtained using LAPEN as the material, while the thickness of the sub-base course pavement layer is 20 – 25 cm. Jalan Harmonika Baru was also widened from 7 meters to 14 meters with 2 ways and 2 lanes.